Online Mini Workshop on Recycled Cardboard Craft with Batik Pattern for Junior High School Students - Gunawan, Irena V; Halim, Erwin Ardianto (Journal of Innovation and Community Engagement, 2022)
Paper is one kind of waste which are abundantly available. Although the use of writing or printing paper is significantly reduced since many writing activities have moved to digital means, however other paper products such as cardboards are significantly increasing. This is a result of the increase in online shopping activities where most of the goods are being delivered in cardboard packages. One of the craft topics for Level 7 of Junior High School from the Indonesian Ministry of Education and Culture includes the recycled paper or other paper products to be transformed into other functions. Hence, cardboard is very suitable to be used as a learning object. As cardboard also has a certain structure which consists of 3 layers of cardboard, the middle is corrugated paper, hence the students could learn to manipulate cardboard into an interesting product. As the workshop was being conducted online there were some techniques that had to be adjusted in terms of material delivery strategies and teaching methods. The workshop method conducted by a community service team consists of university lecturer and university students who gave a mini-workshop session for the 7-grade school students. The students were invited to employ their crafting skills using commonly available recycled cardboard material.